Efektivitas Pelatihan Sistem Informasi Akuntansi Untuk Kesadaran Pengelolaan Keuangan Siswa di SMAN 1 Baros - Nirmala, Naurah Ayu; Nursauma, Rena; Bahtiar, Apendi; Fidita, Fidita; Ramadhani, Anggun Septian (Universitas 17 Agustus 1945 Jakarta, 2025)
Financial literacy is very important for students to be able to understand and manage finances. Lack of understanding of financial management can lead to financial problems in the future. To overcome this problem, financial literacy training for high school students can improve their ability in financial management. SMAN 1 Baros focuses on improving students' financial literacy through interactive and practical training. This training is carried out with an educational approach and the use of financial literacy software. The goal is to deepen students' insight into financial management and improve their ability to manage money properly. The results of this training are expected to strengthen their understanding of financial management and skills in managing money. Evaluation will be carried out through direct application of financial literacy training. Successful financial literacy training can improve students' understanding and help them in better financial management. To strengthen the effectiveness of training, a program is needed that integrates financial literacy into the education curriculum in schools.